Comparison of Validity, Reliability, and Accuracy of the Indonesian Version Ocular Surface Disease Index Questionnaire with Dry Eye Questionnaire-5 in Enforcement Dry Eye Disease Diagnosis - Astuti, Melia Budi; Hasnah, Hasnah; Kasim, Muhammad Firdaus; Sirajuddin, Junaedi (Journal La Medihealtico, 2025)
The Ocular Surface Disease Index (OSDI) questionnaire and Dry Eye Questionnare-5 (DEQ-5) are widely used to evaluate subjective symptoms of dry eye disease (DED) as a primary diagnostic criterion. This study aims to compare the validity, reliability, and accuracy of the Indonesian version of OSDI and DEQ-5 questionnaires. Hospital-based cross-sectional study. A total of 100 participants were enrolled in the study. The Indonesian version of the OSDI and DEQ-5 questionnaires were analyzed to evaluate the validity and reliability of both questionnaires. Then, the accuracy of both questionnaires was compared with the diagnostic test and the receiver operating characteristic curve (AUC) analysis. All the question items on both questionnaires are valid and reliable. The validity test using Pearson’s product-moment correlation coefficient, the value exceeds 0.23 (P<0.01) and the reliability test using Cronbach’s alpha coefficient test showed good and excellent internal consistency for OSDI and DEQ-5 (Cronbach’s alpha of OSDI 0.78 and DEQ-5 0.81). The accuracy of both questionnaires was good and there was no significant difference with AUC OSDI=0.78 and AUC DEQ-5=0.79. The Indonesian version of OSDI and DEQ-5 questionnaires met the validity and reliability requirements so that they were declared valid and reliable as effective instruments for DED assessment in the Indonesian population.